2022
DOI: 10.3389/fnhum.2022.1049572
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric and visual analysis of transcranial direct current stimulation in the web of science database from 2000 to 2022 via CiteSpace

Abstract: ObjectiveThis study aimed to evaluate the current research hotspots and development tendency of Transcranial Direct Current Stimulation (tDCS) in the field of neurobiology from a bibliometric perspective by providing visualized information to scientists and clinicians.Materials and methodsPublications related to tDCS published between 2000 and 2022 were retrieved from the Web of Science Core Collection (WOSCC) on May 5, 2022. Bibliometric features including the number of publications and citations, citation fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…If it was >0.5, clustering was typically considered acceptable. [ 9 ] Another structural metric used to determine cluster quality is modularity. [ 7 ] The modularity score (Q) indicates the extent to which a network can be divided into modules.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If it was >0.5, clustering was typically considered acceptable. [ 9 ] Another structural metric used to determine cluster quality is modularity. [ 7 ] The modularity score (Q) indicates the extent to which a network can be divided into modules.…”
Section: Methodsmentioning
confidence: 99%
“…The WOS is one of the most comprehensive, systematic, and authoritative databases and is one of the most popular databases for scientometric evaluation with complete references and citations. [ 9 , 10 ] Therefore, this study utilized the WOS database for the literature search and employed CiteSpace software to analyze the records. Our findings aim to begin to build a knowledge map of this field and allow scholars and clinicians to better understand the advancement and future directions of this treatment to develop new schemes for higher treatment success rates and to provide better services.…”
Section: Introductionmentioning
confidence: 99%
“…Overly broad exclusion criteria can introduce population bias; insufficient accommodations for individuals who wear head coverings or exhibit sensory processing sensitivity may hinder diverse participation. Many studies, excluding those focusing on disorders prevalent in older adults, predominantly involve young participants and are conducted in a limited number of countries (Sun et al, 2022 ; Medeiros et al, 2023 ; Wang et al, 2023 ).…”
Section: Obstacles To Effective Non-invasive Brain Stimulationmentioning
confidence: 99%
“…Some of the other bibliometric information includes the number of publications, impact factor, H-index, degree of centrality, strength of linkage, year of publication, and occurrence/citation bursts were extracted and analyzed. CiteSpace (6.1.R3) was applied to detect the keywords and references with citation bursts, while the citation bursts included strength and duration and indicated that a paper was highly cited in a certain period [28]. Centrality is based on the theory of social network analysis by counting the number of shortest paths between other nodes in interest [29].…”
Section: Data Extraction and Analysismentioning
confidence: 99%